Bori's on the move - Joyner, Andrew (New York : Scholastic, 2011)
This series is part of Scholastic's early chapter book line called Branches, which is aimed at newly independent readers. With easy-to-read text, high-interest content, fast-paced plots, and illustrations on every page, these books will boost reading confidence and stamina. Branches books help readers grow!Meet Boris! He lives with his mom and dad in Hogg Bay. Their home is a van that once traveled all over the world. Then one morning, Boris feels a jolt. Could it be? Is the van really moving? Is Boris on an adventure at last?But when Boris ends up on a trip to a wildlife refuge instead of the jungle safari he'd imagined, he ends up having an adventure he'll never forget. Because for this little warthog, life never quite turns out as he plans.